A Systematic Literature Review: Blended Learning as the Icon of Excellence in Primary Schools in the Era of the Fourth Industrial Revolution - Avivatul Abidah; Indra Tri Yulistianto; Satrio Ryan Ramadhan; David Yusuf Azwarnaufal; Ida Rindaningsih (Indonesian Journal of Cultural and Community Development, 2023)
This systematic literature review aims to investigate whether blended learning can become the hallmark of educational excellence. The study documents and reviews articles related to blended learning from 2014 to 2021, sourced from accredited national and international journals accessible through Google Scholar, ScienceDirect, and ResearchGate. The results reveal that blended learning plays a crucial role as a solution for teaching and learning activities during the COVID-19 pandemic and the 21st century. It has the potential to become an icon of educational excellence; however, successful implementation requires alignment of institutional goals, educators, students, and parents. The implications of this study underscore the significance of embracing blended learning as a creative and innovative approach to adapt to the challenges of the pandemic and beyond. Highlights: Blended learning as a transformative solution: Blended learning emerges as a vital approach to seamlessly integrate traditional face-to-face teaching with online education, presenting a transformative solution to adapt to the challenges of the COVID-19 pandemic and beyond. Educational excellence in the 21st century: The systematic review showcases blended learning as a potential icon of educational excellence, offering a pathway to foster innovative and creative learning environments that align with the demands of the 21st-century education landscape. Key success factors for implementation: The study emphasizes the significance of goal alignment among institutions, educators, students, and parents, highlighting that successful implementation of blended learning hinges upon the collaboration and synchronization of all stakeholders. Keywords: Blended Learning, Educational Excellence, COVID-19 Pandemic, Systematic Literature Review, Online Education